CNS Anomalies – Antenatal Diagnosis in Quantitative Polyhydramnios - Barlas, Nauman Bashir; Bilal, Ahmed (Annals of King Edward Medical University, 2011)
Excess of amniotic fluid is called polyhydramnios. It is suspected clinically and confirmed by sonography. Criteria of an amniotic fluid pocket of 8 or more than 8 cm measured in anterioposterior direction was taken in this study to quantitate Polyhydramnios. One hundred patients fulfilling this criterion were included in this study. The degree of polyhydranios cor-related directly that an anomaly would be detected on a prenatal sonogram. Purpose of this study was to evaluate the spec-trum and frequency of CNS anomalies in quantitative polyhydramnios. 53 cases were normal where as 47 fetuses were ano-malous. A total of 59 anomalies were detected with some fetuses showing multiple anomalies. CNS anomalies were the com-monest ones encountered in this study. Neural tube defects, hydrocephalus, encephaloceles, meningocele, spina bifida, holo-prosencephaly, and hydranencephaly were some of the anomalies seen. Key Words: Polyhydramnios, Fetal Anomalies.